Determination the causative strain for hydatid cyst in Iraqi cattle by using ND1 gene: Mohammed J. Muhaidi1, Maysam N. Ahmed1 and Mohammed T. Dagash2 - Muhaidi, Mohammed J. (The Iraqi Journal of Veterinary Medicine, 2017)
Hydatid Cysts were obtained from 15 cows from liver, lung, spleen, heart, and peritoneal cavity, between December 2014 and October 2015. Hydatid cysts (protoscoleces) were used for deoxyribonucleic acid extraction by using mechanical grinder. The purification of mtDNA was done by (promega kit, USA). The mitochondrial NADH dehydrogenase subunit 1 (ND1) genes was used as targets for polymerase chain reaction amplification, all hydatid cysts yielded amplification products. Polymerase chain reaction product for NADH1 800 basic pair. The polymerase chain reaction products were purified and partial sequences were generated. The sequences obtained were found to align with corresponding region for ND1 gene in the Gene Bank nucleotide database confirming to genotype of sheep strain (G1) in Iraq, Phylogenetic analysis of partial sequence data from ND1 genes for obtained Phylogenetic tree. G1 genotype was the most common taxon and the actual source of infection of Iraqi's cattle. All of 15 strains were G1 genotype (sheep strain) based on the partial sequences of NADH dehydrogenase 1 (ND1).